2021
DOI: 10.1007/s41748-021-00243-4
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Land Cover Changes on Land Surface Temperature and Human Thermal Comfort in Dhaka City of Bangladesh

Abstract: Urbanization leads to the construction of various urban infrastructures in the city area for residency, transportation, industry, and other purposes, which causes major land use change. Consequently, it substantially affects Land Surface Temperature (LST) by unbalancing the surface energy budget. Higher LST in city areas decreases human thermal comfort for the city dwellers and affects the urban environment and ecosystem. Therefore, a comprehensive investigation is needed to evaluate the impact of land use cha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
38
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 119 publications
(58 citation statements)
references
References 78 publications
4
38
0
Order By: Relevance
“…Phuket Island's urban and built-up areas have been primarily expanded by converting perennial trees and orchards and idle land. This finding is consistent with previous studies [54,55], which stated that most agricultural land and vegetation areas were transformed into urban and built-up areas to meet people's demands, leading to the LULC change.…”
Section: Land Use and Land Cover Assessment And Change Detectionsupporting
confidence: 93%
“…Phuket Island's urban and built-up areas have been primarily expanded by converting perennial trees and orchards and idle land. This finding is consistent with previous studies [54,55], which stated that most agricultural land and vegetation areas were transformed into urban and built-up areas to meet people's demands, leading to the LULC change.…”
Section: Land Use and Land Cover Assessment And Change Detectionsupporting
confidence: 93%
“…The overall accuracy of the LULC maps of these maps achieved with minor error percentage. Error percentage caused due to wrong color detection while creating training samples, which lead to change in area of LULCC [41,42].…”
Section: Results Of Land Use Land Cover Classificationmentioning
confidence: 99%
“…Furthermore, Figure 6 (i, n, p) demonstrates a positive trend, whereas Figure 6 (m, o) demonstrates a decreasing trend and Figure 6 (j, k, l) demonstrates no trend. Some studies also found that NDBI and NDBAI had a positive correlation with LST, while NDWI had a negative correlation with LST [ 71 ].
Figure 5 Scatter plot for NDVI and LST (a–d); NDBI and LST (e–h).
…”
Section: Discussionmentioning
confidence: 99%